TRANSFORMATIONS IN NITRATE PRECURSORS SYSTEMS AT PREPARATORY FORMATION STAGES OF RARE-EARTH ELEMENTS CONTAINING OXIDE FUNCTIONAL MATERIALS - Дрючко, О. Г.; Стороженко, Д. О.; Бунякіна, Н. В.; Іваницька, І. О.; Голубятніков, Д. В.; Китайгора, К. О. (Scientific Progress & Innovations, 2015)
Using the complex of physical chemistry methods the authors studied nature and special features of chemical interaction, thermal transformation (25–1000 oC) of structural components in the system of nitrates of neodymium and potassium as model of the systems of nitrates of rare-earth elements and elements IA of the group of periodic system, ammonium, which are now widely used in the syntheses, the technological regulations of the creation of the functional materials of different designation with the assigned complex of structurally sensitive characteristics. A number of special features and regularities in their joint behavior was discovered.